2007
DOI: 10.1364/oe.15.016954
|View full text |Cite
|
Sign up to set email alerts
|

The effect of structural disorder on guided resonances in photonic crystal slabs studied with terahertz time-domain spectroscopy

Abstract: We measure the normal-incidence transmission coefficient of photonic crystal slabs with hexagonal arrays of air holes in silicon. The transmission spectra exhibit sharp resonant features with Fano line shapes. They are produced due to the coupling of the leaky photonic crystal modes, called guided resonances, to the continuum of free-space modes. We investigate the effects of several types of structural disorder on the spectra of these resonances. Our results indicate that guided resonances are very tolerant t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 0 publications
4
23
0
Order By: Relevance
“…To study photonic band, we employ an out-of-plane illumination scheme ( Fig. 1(b)), which is similar to the experimental setup of the silicon PC [3,4]. The ΓM and ΓK directions are also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To study photonic band, we employ an out-of-plane illumination scheme ( Fig. 1(b)), which is similar to the experimental setup of the silicon PC [3,4]. The ΓM and ΓK directions are also shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Lots of research focused on the transmission properties for out-ofplane propagations through silicon PC due to the low loss property of silicon in THz range. From the angular variation of the transmission spectra, the photonic band structure for the guided resonances can be found, which can benefit to the development of photonic devices [2][3][4][5]. Compared with the silicon PC, the metal PC slabs (also called metal holes array, MHA) show the unique characteristics in the microwave and THz range due to their influence on the electric field of electromagnetic wave.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is known that they are intrinsically robust with respect to the hole size imperfections and interface roughness in the PC slab (thereby resulting in a higher yield for a given fabrication process), 23 it was also demonstrated that structural random disorder in the hole positions strongly broadens the resonant line shapes in the transmission spectrum, up to their complete disappearance 23 (see Fig. 4).…”
Section: Guided Resonances In Photonic Quasi-crystalsmentioning
confidence: 99%
“…A PC is composed of dielectric materials with a periodic refractive index distribution. In the THz region, PC slabs [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and their applications such as planar low-loss waveguide have been demonstrated [32]. High-Q THz PC micro-cavities (approximately 1000-9000) [25,29,30,34] and their applications in sensing have been recently reported [30,34].…”
Section: Introductionmentioning
confidence: 99%